2019
DOI: 10.31219/osf.io/tdh8k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Financial Development and Energy Consumption Nexus in Malaysia: A Multivariate Time Series Analysis

Abstract: Despite a bourgeoning literature on the existence of a long-run relationship between energy consumption and economic growth, the findings have failed to establish clearly the direction of causation. A growing economy needs more energy, which is exacerbated by growing population. Evidence suggests that financial development can reduce overall energy consumption by achieving energy efficiency. Economic growth and energy consumption in Malaysia have been rising in tandem over the past several years. The three pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 15 publications
12
124
1
1
Order By: Relevance
“…Recent study by, Islam et al (2013) working in Malaysia suggested that energy consumption is influenced by economic growth and financial development, both in short-run and long-run, but the population-energy relationship holds only in the long run 1 .…”
mentioning
confidence: 99%
“…Recent study by, Islam et al (2013) working in Malaysia suggested that energy consumption is influenced by economic growth and financial development, both in short-run and long-run, but the population-energy relationship holds only in the long run 1 .…”
mentioning
confidence: 99%
“…The coefficient demonstrates that there is 0.47% reduction of energy consumption per capita for every 1% increase in loan. This relation implies that financial development, represented by the loan ratio, promotes the usage of efficient energy since the fund is used to purchase newest appliances, so that the energy consumption becomes more efficient [14] [15]. In the last model, it can be seen that variables of energy consumption and population statistically give significant influence to the carbon emissions.…”
Section: A Dynamic Panel Data Resultsmentioning
confidence: 98%
“…The plots of the residuals were in between the 5 percent critical bounds for Model 1, Model 2 and Model 3 even though, there was a slight deviation between the year 2010 to 2011 in the Model 3. There was no structural break after further test was conducted using the Chow test as suggested by Islam, Shahbaz, Ahmed & Alam (2013).…”
Section: Methodsmentioning
confidence: 99%